Built to last : successful habits of visionary companies - Collins, James C. (James Charles), 1958-; Porras, Jerry I. (New York : HarperBusiness, 2002)
Presenting new insight into such companies as 3M, Walt Disney, and General Electric, a study on what makes companies successful examines their flexibility, ideology, and strong purpose.
The best of the best -- Clock building, not time telling -- -- Interlude: No "Tyranny of the OR" -- More than profits -- Preserve the core/stimulate progress -- Big hairy audacious goals -- Cult-like cultures -- Try a lot of stuff and keep what works -- Home-grown management -- Good enough never is -- The end of the beginning -- Building the vision -- Epilogue: Frequently asked questions.
Reprint. Originally published: c1994.
Includes bibliographical references and index.
Keywords: Success in business -- United States; Industrial management -- United States; Entrepreneurship -- United States